2013
DOI: 10.1080/15524256.2013.846891
|View full text |Cite
|
Sign up to set email alerts
|

Hospice Caregiver Depression: The Evidence Surrounding the Greatest Pain of All

Abstract: Terminal illness affects the entire family, both the one with the illness and their loved ones. These loved ones must deal not only with the loss but with the challenges of managing daily care. The purpose of the systematic review of the peer-reviewed literature was to identify and explore depression and related interventions for caregivers of hospice patients. While the prevalence of depression reported in the identified studies of hospice caregivers ranges from 26–57%, few interventions specific to this popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…16 Informal caregivers have high rates of depression, anxiety, and grief, and in the few studies that have focused on their experiences, pain management for their charges has been the most commonly expressed concern. 17 …”
Section: Introductionmentioning
confidence: 99%
“…16 Informal caregivers have high rates of depression, anxiety, and grief, and in the few studies that have focused on their experiences, pain management for their charges has been the most commonly expressed concern. 17 …”
Section: Introductionmentioning
confidence: 99%
“…But it may also be owing to the less severe disease phenotype which made survival for a longer duration possible and lesser complications. Study by Parker et al which involved assessment of anxiety among caregivers of terminally ill patients showed that 33% of the caregivers had anxiety 39 . Indicators of high anxiety levels in this study were young age and severity of disease in patients.…”
Section: Discussionmentioning
confidence: 42%
“…2 Nearly one-third of family caregivers of patients receiving hospice care report they are moderately to severely anxious and/or depressed. 3 Research has shown that hospice caregivers are seeking additional information related to patient care, pain and symptom management, and self-care. 3 Caregivers need education and assistance to make patient-centered and family-centered care a reality for hospice patients.…”
Section: Introductionmentioning
confidence: 99%
“…3 Research has shown that hospice caregivers are seeking additional information related to patient care, pain and symptom management, and self-care. 3 Caregivers need education and assistance to make patient-centered and family-centered care a reality for hospice patients. 4…”
Section: Introductionmentioning
confidence: 99%